Barriers and opportunities related to access to oncology care in Benin: a qualitative study on breast cancer - Clémence Schantz; Freddy Houéhanou Rodrigue Gnangnon; Moufalilou Aboubakar; Anthelme Kouessi Agbodande; Paloma Puig; Justin Lewis Denakpo; Angéline Tonato Bagnan; Marie Bottin; Komi Mena Agbodjavou; Hélène Robin Sacca; Luis Teixeira; Valéry Ridde; et al. (BMC Cancer)
Abstract Background Breast cancer is the most prevalent cancer among women globally, including in Africa. Oncology is a relatively new discipline in many West African countries, particularly in Benin. There is currently a lack of data concerning the current state of cancer care infrastructure and oncology practices within these countries. The aim of the article is to describe the barriers and opportunities related to access to oncology care in Benin. Methods We employed a qualitative research design. Fifty-six semi-structured interviews were conducted with caregivers treating cancer (n=26), women with breast cancer (n=23), and representatives of associations (n=2). Additionally, 18 days of participant observation were conducted in a chemotherapy and palliative care departments in Cotonou, Benin. The data was analysed using Levesque et al.‘s theoretical framework on access to healthcare. Results Women encounter obstacles such as delayed diagnosis and unequal access to information, as well as socio-cultural beliefs that favour traditional medicine and discourage surgical interventions like mastectomy. The treatment pathway is often chaotic due to insufficient specialised caregivers and limited infrastructure, with services centralised in Cotonou forcing patients to travel long distances around the country. The current lack of radiotherapy requires patients in need to travel abroad for treatment. High costs of biomedical tests and treatments often lead to care abandonment, worsening health inequalities. However, positive changes should be highlighted, such as the establishment of the Inter-University Diploma in Gynaecological and Breast Oncology in 2013, the expansion of palliative care services in the country, and the planned opening of the Calavi International Hospital Centre in 2025. Challenges include continuing to train health professionals in oncology, further developing health financing and supporting civil society to raise awareness of breast cancer. Conclusions Benin is facing several challenges in relation to the provision of timely and high-quality care for women with breast cancer. However, there is a growing commitment to enhancing breast cancer care in Benin.